2019
DOI: 10.1002/pi.5946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbranched poly(citric polyethylene glycol) with various polyethylene glycol chain lengths on starch plasticization and retrogradation

Abstract: A series of hyperbranched poly(citric polyethylene glycol) (PCPEG) materials with varied polyethylene glycol (PEG) chain lengths as plasticizers were mixed with maize starch (MS) via cooking and film‐forming. The structure, pasting property, plasticization, aging property, moisture absorption and compatibility of plasticized starches were studied by means of Fourier transform infrared spectroscopy, X‐ray diffraction, rapid viscosity analysis, tension testing, moisture absorption measurements and scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In recent findings, it has been indicated that hyper-branched polymers can serve as a better plasticizing system for starch as they provide flexibility and concurrently inhibit moisture absorption in the films. Zhang et al reported the use of hyperbranched poly(citric polyethylene glycol) as novel plasticizers for maize starch-based films [ 13 ]. In their work, it was demonstrated, that apart from the hydrogen bond-forming ability, such hyperbranced polymer plasticizers impose a physical entanglement of both starch and plasticizer chains and creates steric hindrance, which more effectively inhibits retrogradation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent findings, it has been indicated that hyper-branched polymers can serve as a better plasticizing system for starch as they provide flexibility and concurrently inhibit moisture absorption in the films. Zhang et al reported the use of hyperbranched poly(citric polyethylene glycol) as novel plasticizers for maize starch-based films [ 13 ]. In their work, it was demonstrated, that apart from the hydrogen bond-forming ability, such hyperbranced polymer plasticizers impose a physical entanglement of both starch and plasticizer chains and creates steric hindrance, which more effectively inhibits retrogradation.…”
Section: Introductionmentioning
confidence: 99%